Síndrome cardiorrenal em cães: revisão de literatura - Lima, Yumi Nagasawa (Universidade Estadual Paulista (Unesp), 2022)
The cardiorenal syndrome (CRS) corresponds to the pathophysiological interaction between the cardiovascular and renal systems, of acute or chronic manifestation and, induced by dysfunction in one of these systems, in both or from an external systemic condition. It includes pathophysiological mechanisms and axis not fully understood yet in veterinary medicine. The most common etiologies of cardiovascular and renal dysfunctions are highly variable between species, possibly limiting the correlation between cardiorenal syndrome studies in human patients and small animals such as dogs and cats. The Cardiovascular-Renal Disorders Consensus Group suggested the term 'cardiovascular-renal disorders' to refer to a cardiorenal syndrome in veterinary medicine and classified it considering the organ responsible for the dysfunction which triggers the syndrome, its progression axis, and the characteristic of its manifestation. Some recognized etiologies include mechanisms that can interfere with the functioning of both cardiovascular and renal systems and possibly link the pathophysiological axis of this syndrome through a complex interaction. Neurohumoral mechanisms, which lead to intense and persistent activation of sympathetic and renin-angiotensin-aldosterone systems, may participate in more than one pathophysiological axis in the cardiorenal syndrome. To determine the possible main mechanisms of CRS may be the first step to improving understanding of this complex clinical manifestation. The objective of this study is to describe the classification and mechanisms involved in cardiorenal syndrome in dogs

A síndrome cardiorrenal (SCR) corresponde à interação fisiopatológica entre os sistemas cardiovascular e renal, de manifestação aguda ou crônica e, com origem em disfunção de um desses sistemas, de ambos ou em condição sistêmica independente. Envolve mecanismos e vias fisiopatológicas ainda não totalmente esclarecidos na medicina veterinária. As etiologias mais comuns da disfunção cardiovascular e da disfunção renal são bastante variáveis entre espécies, o que possivelmente limita a correlação entre estudos sobre a síndrome cardiorrenal em pacientes humanos e pequenos animais, como cães e gatos. O Cardiovascular-Renal Axis Disorders Consensus Group sugeriu o termo ‘cardiovascular-renal disorders’ para se referir à síndrome cardiorrenal na medicina veterinária e elaborou uma classificação considerando o órgão responsável pelo distúrbio que deflagra a síndrome, seu eixo de progressão e a característica de sua manifestação. Algumas etiologias reconhecidamente envolvem mecanismos que podem interferir no funcionamento tanto do sistema cardiovascular quanto do sistema renal e possivelmente unem o eixo fisiopatológico da síndrome através de interações complexas. Mecanismos neuro-humorais que cursam com ativação intensa e persistente do sistema simpático e do sistema renina-angiotensina-aldosterona possivelmente participam de mais de uma via fisiopatológica da síndrome cardiorrenal. Definir quais os possíveis mecanismos centrais da SCR pode ser o primeiro passo para melhorar o entendimento dessa manifestação clínica complexa. O objetivo do estudo foi abordar a classificação e os mecanismos envolvidos na síndrome cardiorrenal em cães.
Cardiorenal syndrome in dogs: literature review
Keywords: Cardiorenal syndrome; Pathophysiology; Cardiovascular system; Fisiopatologia; Sistema cardiovascular; Rins doenças; Síndrome cardiorrenal